Searching for avidity by chemical ligation of combinatorially self-assembled DNA-encoded ligand libraries - Matysiak, S; Hellmuth, K; El-Sagheer, A; Shivalingam, A; Ariyurek, Y; de Jong, M; Hollestelle, M; Out, R; Brown, T (Royal Society of Chemistry, 2017)
DNA encoded ligands are self-assembled into bivalent complexes and chemically ligated to link their identities. To demonstrate their potential as a combinatorial screening platform for avidity interactions, the optimal bivalent aptamer design (examplar ligands) for human alpha-thrombin is determined in a single round of selection and the DNA scaffold replaced with minimal impact on the final design.